Experimental studies on medical treatments of retinal dystrophies with a particular focus on ABCA4 retinopathies - Ścieżyńska, Aneta; Oziębło, Dominika; Ołdak, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Retinal dystrophies are a group of hereditary diseases varying in clinical and etiological aspects. The most common central retinal dystrophy is Stargardt’s disease, which is mainly caused by mutations in the ABCA4 gene. Dysfunction of the ABCA4 gene product leads to accumulation of toxic metabolites of the visual cycle and consequently to the loss of photoreceptors and surrounding retinal pigment epithelial cells. This study summarizes various pharmacological attempts aimed at slowing the progression of retinal dystrophies, especially ABCA4 retinopathies.